2015
DOI: 10.1111/nuf.12118
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity: A Concept Analysis

Abstract: Aim To report an analysis of the concept of food insecurity, in order to 1) propose a theoretical model of food insecurity useful to nursing and 2) discuss its implications for nursing practice, nursing research, and health promotion. Background Forty eight million Americans are food insecure. As food insecurity is associated with multiple negative health effects, nursing intervention is warranted. Design Concept Analysis Data sources A literature search was conducted in May 2014 in Scopus and MEDLINE us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 72 publications
1
44
0
1
Order By: Relevance
“…The results of this study were similar to studies of schoolchildren that found those who are from higher food insecurity families to present higher caries rates (10,12). The correlation between food insecurity and dental caries may be attributed to the dietary behaviors of these families that may include diets high in easily fermentable carbohydrates in order to provide the children with the necessary energy (8). Also, food insecurity may restrict people's food choices leading to purchasing unhealthy and highly cariogenic foods that are lower in cost and nonperishable.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results of this study were similar to studies of schoolchildren that found those who are from higher food insecurity families to present higher caries rates (10,12). The correlation between food insecurity and dental caries may be attributed to the dietary behaviors of these families that may include diets high in easily fermentable carbohydrates in order to provide the children with the necessary energy (8). Also, food insecurity may restrict people's food choices leading to purchasing unhealthy and highly cariogenic foods that are lower in cost and nonperishable.…”
Section: Discussionsupporting
confidence: 85%
“…Food insecurity has multiple characteristics as a concept and affects different levels in our society. One aspect is related to the quantity of food that someone has, based on his income, occupation and his ability to buy or produce enough food . Another aspect of food insecurity is access to food that is safe to consume .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short questionnaires (eg, 2-items) are available that can identify those at risk of experiencing food insecurity. [30][31][32] In turn, these patients can be connected to support services, such as the charitable food system (eg, food banks, food pantries) and federal nutrition assistance programs. Furthermore, food insecurity screenings can help identify patients who may face barriers (eg, poor nutrition and diet quality, reduced medication adherence) and medical complications (eg, emergency department visits, hospitalizations) that compromise obesity treatment and management.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of information related to food insecurity in nursing students is a current gap in knowledge and in the scientific literature. It is important that faculty, administrators, and other nurses acknowledge that our future nurses currently in universities across the world may also struggle with this filling this basic human need of having regular nutritious meals 9 …”
Section: Introductionmentioning
confidence: 99%